ORGANIZATIONAL CULTURE AND ITS ROLE IN ENHANCING JOB PERFORMANCE WITHIN THE WORKPLACE - Afifa Ladjel; Zoubiri Abdallah (International Journal of Innovative Technologies in Social Science, 2025)
The study aimed to analyze the impact of organizational culture on job performance within the work environment by examining the institutional cultural dimensions and their reflection on employee behavior and productivity levels,it also sought to identify the main elements of organizational culturesuch as values, beliefs, norms and organizational symbolsand to assess their contribution to improving the quality of job performance, The study was based on relevant theoretical literature addressing the concepts of organizational culture and job performance in terms of their characteristics, significance, determinants, components, types and dimensions,it also focused on the role of organizational culture in enhancing or diminishing job performance by studying its effects on both employees and the organization, In light of the study’s questions and hypotheses the findings revealed a clear relationship between organizational culture and job performance it was found that embedding organizational culture within the work environmentparticularly through the role of organizational leadershipeffectively contributes to enhancing productivity and creating a positive work environment. Ultimately, the study concluded with a set of general findings confirming the importance of developing organizational culture as a means to improve performance within institutions.